Patent System of Taxation in the Russian Federation: Problems of Application and Development Prospects - Marselovna Galimardanova, Yulia (2021)
Currently, the implementation of support and ensuring the development of small and medium-sized businesses in the Russian Federation is one of the most important tasks of the state. The primary task of state tax regulation is to ensure such a mechanism for taxing the activities of small and medium-sized businesses, in which, on the one hand, the optimal level of tax burden is ensured, and on the other hand, there are stable and predictable tax revenues to the budget system. One of the tools of tax regulation are special tax regimes that provide support and development of small and medium-sized businesses, simplify the mechanism of taxation and tax administration, and optimize the tax burden. One of such special tax regimes is the patent taxation system.